Teatro Comparado, territorialidad y espectadores: multiplicidades intraterritoriales (El Hilo de la Fabula, 2020)
The Comparative Theater and the concepts of territoriality, inter–territoriality, intra–territoriality and supra–territoriality enable a new design of the theatrical cartography, demanded today by the indispensable updating of the Theatrology. Territoriality considers theater in geographical–historical–cultural contexts of relationship and difference when they are contrasted with other contexts. There are two fundamental types of theatrical territoriality: a geographical territoriality and a corporal one. The comparative territoriality is conceived as a subjective space, a space constructed from processes of territorialization (processes of subjectivation), de-territorialization and re–territorialization. As an example of intraterritorial complexity, this article analyzes the responses of spectators in Buenos Aires, in 2013, to the concept of «commercial art theater».
Keywords: Comparative Theater; Territoriality; Space; Subjectivity.; Spectators